From financial wealth shocks to ill‐health: Allostatic load and overload. (16th January 2023) - French, Declan
Abstract: A number of studies have associated financial wealth changes with health‐related outcomes arguing that the effect is due to psychological distress and is immediate. In this paper, I examine this relationship for cumulative shocks to the financial wealth of American retirees using the allostatic load model of pathways from stress to poor health. Wealth shocks are identified from Health and Retirement Study reports of stock ownership along with significant negative discontinuities in high‐frequency S&P500 index data. I find that a one standard deviation increase in cumulative shocks over two years increases the probability of elevated blood pressure by 9.5%, increases waist circumference by 1.2% and the cholesterol ratio by 6.1% for those whose wealth is all in shares. My findings suggest that the combined effect of random shocks to financial wealth over time is salient for health outcomes. This is consistent with the allostatic load model in which repeated activation of stress responses leads to cumulative wear and tear on the body.